California - Dorling Kindersley (London : Dorling Kindersley Limited, 2000)
"This guide is all you need to experience the magnificent landscape and culture of California. Here you can find everything from the glitz and glamour of Hollywood to the thrills of theme parks; from laid-back surf beaches to bustling cities such as Los Angeles and San Francisco; and from Silicon Valley to Death Valley and Yosemite National Park. The guide is packed with over 1,500 photographs, illustrations and maps, plus top recommendations on where to eat, stay and shop." -- Amazon.
How to use this guide -- Introducing California -- Los Angeles -- Southern California -- San Francisco and the Bay Area -- Travellers' Needs -- Survival Guide -- Practical information -- Travel information -- General index -- Acknowledgements -- Road map.
Includes index.
Keywords: CALIFORNIA -- GUIDEBOOKS